2005
DOI: 10.1128/jb.187.24.8450-8461.2005
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Twin-Arginine Translocation System in Pseudomonas syringae pv. tomato DC3000 and Its Contribution to Pathogenicity and Fitness

Abstract: The bacterial plant pathogen Pseudomonas syringae pv. tomato DC3000 (DC3000) causes disease in Arabidopsis thaliana and tomato plants, and it elicits the hypersensitive response in nonhost plants such as Nicotiana tabacum and Nicotiana benthamiana. While these events chiefly depend upon the type III protein secretion system and the effector proteins that this system translocates into plant cells, additional factors have been shown to contribute to DC3000 virulence and still many others are likely to exist. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 69 publications
(75 reference statements)
1
51
0
Order By: Relevance
“…Moreover, virtually all phospholipase C orthologs in a wide variety of organisms have predicted Tat signal sequences (16), and there are bacterial Plc enzymes proven to be exported by the Tat pathway (9,36,46,60). In contrast to what was seen in M. smegmatis, when expressed in M. tuberculosis two species of PlcB-HA were evident by immunoblot analysis.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Moreover, virtually all phospholipase C orthologs in a wide variety of organisms have predicted Tat signal sequences (16), and there are bacterial Plc enzymes proven to be exported by the Tat pathway (9,36,46,60). In contrast to what was seen in M. smegmatis, when expressed in M. tuberculosis two species of PlcB-HA were evident by immunoblot analysis.…”
Section: Discussionmentioning
confidence: 65%
“…In several bacterial pathogens, the Tat pathway plays an important role in exporting virulence factors (9,10,17,30,36,42,46,60). Mycobacterium tuberculosis is the bacterial pathogen re-sponsible for tuberculosis, which kills 1.8 million people a year (64).…”
mentioning
confidence: 99%
“…Tat secretion has been shown to be important for the motility of the gram-negative pathogens P. aeruginosa, P. syringae pv. tomato DC3000, E. coli O157:H7, and Agrobacterium tumefaciens (11,21,43,50). In the latter two cases, the Tat-defective strains have been shown not to express flagellin, indicating that components of the flagellar secretion assembly and/or secretion system are Tat substrates.…”
Section: Resultsmentioning
confidence: 99%
“…However, the Tat system has also been shown to be involved in secretion of virulence determinants like phospholipase toxins in Pseudomonas aeruginosa (43,69), P. syringae pv. tomato DC3000 (11), and Legionella pneumophila (56), as well as Shiga toxin 1 in enterohemorrhagic E. coli (50).…”
mentioning
confidence: 99%
“…Several studies indicate that a functional Tat system is required for many pathogenic bacteria, such as Pseudomonas syringae pv. tomato DC3000, S. enterica, Campylobacter jejuni, and Ralstonia solanacearum (5,(48)(49)(50)(51), to efficiently re- spond to diverse forms of physicochemical stresses. Indeed, our transcriptomic analysis of the Y. pseudotuberculosis ⌬tatC mutant revealed that a number of prominent stress-responsive genes were induced at both temperatures, and this number was higher during stationary-phase growth.…”
Section: Figmentioning
confidence: 99%